Polyphenol Content and Antioxidant Evaluation of Kawista (Limonia acidissima) Leaf Extract - Fawwaz, Muammar; Pratama, Mamat; Razak, Rais; Andika, Yusrianti; Astika, Elvina; Feralia, Feralia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Kawista or Limonia acidissima, a plant traditionally used by the Bima community, offers potential health benefits. This study aimed to evaluate the antioxidant potential of ethanol extract from L. acidissima leaves by determining total flavonoid content (TFC), total phenolic content (TPC), and antioxidant activity using DPPH, FRAP, and CUPRAC assays. The ethanol extract exhibited significant antioxidant activity, with IC50 values of 10.445 and 135.42 µg/mL for DPPH and CUPRAC assays, respectively. TPC and TFC were determined to be 14.63 mgGAE/g extract and 113.9 mgQE/g extract, respectively. These findings suggest that L. acidissima leaf extract possesses potent antioxidant properties, which may be attributed to its flavonoid and phenolic content. Further research is warranted to explore this plant extract's underlying mechanisms of action and potential therapeutic applications.